2019
DOI: 10.1088/1742-6596/1378/3/032039
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Academic Performance in Engineering: An Empirical Study in a Leading Nigerian University

Abstract: Engineering is increasingly becoming a more popular career for women globally. This study aims at examining the performances of female students in comparison to their male counterparts. This is then used to determine if there is any correlation in their performances. The sample population for this research is the engineering students in Covenant University, a leading University in Nigeria. The performance of the graduating students in this school over 11 years, from 2006 to 2017, was analysed and studied. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Foreign studies devoted to the analysis of sex and age characteristics in the learning process (Hirnstein et al, 2019;Hardebolle et al, 2022;Fényes, 2014;Abioye et al, 2019) specify that the existing differences between male and female students can manifest themselves at the cognitive, behavioral and physical levels. In particular, the process of learning English brings the properties of memory and cognitive activity of students to the forefront (Bećirović et al, 2021), which are inextricably linked with their age characteristics.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Foreign studies devoted to the analysis of sex and age characteristics in the learning process (Hirnstein et al, 2019;Hardebolle et al, 2022;Fényes, 2014;Abioye et al, 2019) specify that the existing differences between male and female students can manifest themselves at the cognitive, behavioral and physical levels. In particular, the process of learning English brings the properties of memory and cognitive activity of students to the forefront (Bećirović et al, 2021), which are inextricably linked with their age characteristics.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The involvement of women in engineering programs holds significant importance in cultivating diversity and inclusivity in this field (Porter & Serra, 2020). Supporting more women to take engineering programs enables engineering schools to achieve substantial developments and fosters an environment making an innovative electronics engineering program (Abioye et al, 2019). In the study of Jung and Kim (2020), it is reported that mixed-gender or diverse teams are generally successful and create patents more frequently than singlegender teams.…”
Section: Introductionmentioning
confidence: 99%